2006
DOI: 10.1097/01.mcp.0000245704.92311.1e
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in neuromuscular diseases

Abstract: A nap of less than 30 min duration during the day promotes wakefulness and enhances performance and learning ability. In contrast, the habit of taking frequent and long naps may be associated with higher morbidity and mortality, especially among the elderly. The benefits of napping could be best obtained by training the body and mind to awaken after a short nap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 35 publications
2
33
0
1
Order By: Relevance
“…Our study suggests that the prevalence of SDB in FSHD, and the respiratory patterns observed during sleep, closely resemble those observed in Duchenne's and Becker's muscular dystrophies [6,7,9,10], in myotonic dystrophy [6,11] and in limb-girdle muscular dystrophy [12]. There are no systematic data available in literature concerning SDB in FSHD [31,32].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study suggests that the prevalence of SDB in FSHD, and the respiratory patterns observed during sleep, closely resemble those observed in Duchenne's and Becker's muscular dystrophies [6,7,9,10], in myotonic dystrophy [6,11] and in limb-girdle muscular dystrophy [12]. There are no systematic data available in literature concerning SDB in FSHD [31,32].…”
Section: Discussionsupporting
confidence: 70%
“…The involvement of respiratory muscles is uncommon: Wohlgemuth et al [5] esteemed that only 1% of Dutch patients with FSHD suffered from respiratory insufficiency which required nocturnal ventilatory support. Sleep disordered breathing (SDB) is common in muscular dystrophies [6][7][8]; it has been described in Duchenne muscular dystrophy [6,7,9,10], in myotonic dystrophy [6,7,11] and in limb-girdle muscular dystrophy [12]. SDB may consist in central alveolar hypoventilation [6][7][8]11,13], upper airways obstruction due to pharyngeal muscle weakness [6,11] or thoracic restrictive pathology due to kyphoscoliosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea syndrome (OSAS) is common in muscular dystrophies: it has been described in Duchenne muscular dystrophy [6][7][8][9], in myotonic dystrophy [6,7,10,11], and in limb-girdle muscular dystrophy [12]. In a previous paper [13], we investigated the presence of sleepdisordered breathing (SDB) in 51 consecutive patients with genetically proven FSHD by means of nocturnal polysomnography.…”
Section: Introductionmentioning
confidence: 99%
“…However, when WNK1 was added to the coexpression cocktail, the WNK4 inhibitory effect of the NCC was lost. Later on, Subramanya et al [56] analyzed the effect of the L-WNK1 and S-WNK1 variants of WNK1 upon the NCC and its WNK4 regulation. Their observations are very important to understand the mechanism by which increased expression of a normal L-WNK1 in PHAII patients produces increased activity of the NCC.…”
Section: Modulation Of Renal Ion Transport Systems By Wnksmentioning
confidence: 99%